Simultaneous Determination and Characterization of Tannins and Triterpene Saponins from the Fruits of Various Species of Terminalia and Phyllantus emblica Using a UHPLC-UV-MS Method: Application to Triphala - Avula, Bharathi; Wang, Yan-Hong; Wang, Mei; Shen, Yun-Heng; Khan, Ikhlas A. (Planta Medica, 2013)
Terminalia species are a rich source of tannins. Many preparations of these species are used in traditional medicine and have many different ethnobotanical applications. A simple UHPLC method was developed for the simultaneous analysis of such hydrolysable tannins and triterpene saponins from the fruit rinds of different species of Terminalia (T. chebula, T. arjuna, T. bellirica) and Phyllantus emblica. A separation by LC was achieved using a reversed-phase column and a water/acetonitrile mobile phase, both containing formic acid, using a gradient system and a temperature of 40 °C. Eight hydrolysable tannins (gallic acid, gallic acid methyl ester, corilagin, chebulagic acid, 1,2,3,6-tetra-O-galloyl-β-D-glucose, ellagic acid, chebulinic acid, and 1,2,3,4,6-penta-O-galloyl-β-D-glucose) and six triterpene saponins (arjunglucoside-I, arjunglucoside-III, chebuloside II, bellericoside, arjunetin, and arjunglucoside-II) could be separated within 20 minutes. The wavelength used for detection with the diode array detector was 254 and 275 nm for tannins and 205 nm for triterpene saponins. The method was validated for linearity, repeatability, limits of detection, and limits of quantification. The developed method is economical, fast, and especially suitable for quality control analysis of tannins and triterpene saponins in various plant samples and commercial products of Terminalia.
Keywords: Terminalia; Combretaceae; Phyllantus emblica; tannins; triterpene saponins; UHPLC-UV-MS